Price Effects of the Austrian Fuel Price Fixing Act: A Synthetic Control Study - Maike Becker; Gregor Pfeifer; Karsten Schweikert (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Fuel prices are commonly perceived to be excessively high, which regularly triggers political discussions about fuel price regulations. Consumers demand stricter fuel price regulations to provide transparency about the current price level and to protect them from sudden price fluctuations. Such regulations are already in place in several countries, but whether they indeed help lower the overall fuel price level is unclear. In this paper, we study the effect of Austria's Fuel Price Fixing Act on gasoline and diesel price levels. Using the synthetic control method, we construct a counterfactual and estimate Austria's price trends in absence of the intervention. Our empirical results suggest, that immediately after the Fuel Price Fixing Act came into effect, gasoline prices are 23.4% lower than the synthetic control predicts. The effect on diesel prices appears to be less pronounced and amounts to 6.6% lower prices. Austria's fuel price regulation seems to have been effective in terms of gasoline prices but may need further refinements to effectively tackle diesel prices as well.
Keywords: C22; D43; Q41; 330; causal effects; diesel; gasoline; price regulation; retail fuel prices